Cold spraying ceramic coating and preparation method thereof
Through the cross-linking reaction between organic titanium cross-linking agent and ceramic coating system, the problem of preheating of ceramic coating construction is solved, and cold spraying construction without preheating is achieved, ensuring smooth coating, gloss and water resistance, and solving coating Problems of poor layer flatness and gloss.
Patent Information
- Application Number
- CN202411453701.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2044-10-17
AI Technical Summary
The construction of ceramic coatings requires preheating of the substrate, which leads to inconvenience in construction. The prior art realizes the problem of poor coating flatness and gloss during normal temperature construction by increasing viscosity and adding anti-sag additives.
The organic titanium crosslinking agent is used to cross-link with the ceramic coating system to adjust the pH value of the coating to prepare cold sprayable ceramic coatings to ensure that the paint film is leveled and cross-linked after spraying at room temperature, avoid sagging, and improve coating adhesion and glossiness of the layer.
A ceramic coating can be directly sprayed without preheating, ensuring that the coating is flat and the gloss is not affected, and the water resistance and cross-link density of the coating are improved.
Smart Images

Figure BDA0005089869110000071 
Figure BDA0005089869110000081 
Figure BDA0005089869110000091
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ceramic materials, and in particular relates to a cold spray ceramic coating and a preparation method thereof. Background Art
[0002] Ceramic coatings are usually made by the sol-gel method to react organic and inorganic substances, thus combining the advantages of both new water-based coatings. They are mainly used in cooking utensils, small household appliances, curtain wall decorative panels and other fields. Although ceramic coatings have excellent characteristics such as high hardness, good wear resistance, non-flammable and smokeless, healthy and environmentally friendly, their construction process is relatively complicated. For example, ceramic coatings are water-based coatings with low viscosity and easy to sag during construction. Therefore, in order to prevent the sagging phenomenon of ceramic coatings, the substrate must be preheated to 45-60°C during construction. The preheating temperature also needs to be accurately controlled. If the temperature is too high, the paint film will dry and the leveling will be poor, affecting the appearance and performance of the coating; if the preheating temperature is too low, the paint film will not be thick, which will also affect the performance of the coating. The above-mentioned process of ceramic coatings has high requirements for construction personnel and increases costs for users. Compared with organic coatings, the construction is extremely inconvenient, which seriously affects the use and promotion of ceramic coatings.
[0003] Based on the above problems, it is urgent to solve the process of preheating the substrate before the construction of ceramic coatings and invent a ceramic coating that can be cold-sprayed.
[0004] After searching the existing patent documents, it was found that the authorized invention patent CN202210182024.8 discloses a ceramic coating that can be applied at room temperature and has low unit consumption, and its preparation and application method, which solves the problem of normal temperature construction by increasing the viscosity of the ceramic coating and adding a thixotropic agent. CN201510332612.5 discloses a ceramic film coating that can be sprayed at room temperature, which solves the problem of normal temperature construction by adding an anti-sagging agent. The principles of the above two patents for solving the problem of normal temperature construction of ceramic coatings are basically the same, both of which prevent sagging by increasing the viscosity of the coating and reducing the leveling time of the coating. However, the above technical solutions will bring a series of defects: (1) Due to the high viscosity of the coating and the short leveling time, the flatness of the coating is not good, which will affect the appearance and decorativeness of the coating; (2) The added anti-sagging agent or thixotropic agent will reduce the gloss of the coating, which will also affect the appearance and decorativeness of the coating. Summary of the invention
[0005] The purpose of the present invention is to overcome the inconvenience caused by the need to preheat the substrate to 45-60°C during the construction of the ceramic coating in the above-mentioned prior art, and to prevent sagging by increasing the viscosity of the coating and reducing the leveling time of the coating to achieve the problems of poor coating flatness and poor glossiness caused by normal temperature construction, and to provide a cold spray ceramic coating and a preparation method thereof. The cold spray ceramic coating of the present invention can be constructed in the same way as organic coatings. The substrate does not need to be preheated before construction and can be sprayed directly. Even if the substrate is suspended for spraying, it will not sag, and will not affect the flatness and gloss of the coating.
[0006] The objective of the present invention is achieved through the following technical solutions:
[0007] <First aspect>
[0008] The present invention provides a cold spray ceramic coating, which has a primer and a topcoat;
[0009] Based on 100% of the total mass of the primer, the primer composition is as follows: silica sol: 26-28%, 1% NaOH solution: 4-5%, pigment: 10-12%, filler: 8-10%, hydroxyethyl cellulose aqueous solution: 4-5%, dispersant: 1-1.5%, methyltrimethoxysilane: 20-22%, acetic acid: 5-6%, leveling agent: 1-2%, organic titanium crosslinking agent: 1-2%, wetting agent for organic titanium crosslinking agent: 1-2%, and deionized water: the balance;
[0010] Based on 100% of the total mass of the topcoat, the topcoat is composed of: silica sol: 38-40%, methyltrimethoxysilane: 30-32%, acetic acid: 5-6%, leveling agent: 3-4%, non-stick additive: 3-4%, organic titanium crosslinking agent: 1-2%, wetting agent for organic titanium crosslinking agent: 1-2%, and deionized water: the balance.
[0011] As an embodiment, the organic titanium cross-linking agent is an aqueous titanate complex.
[0012] As an embodiment, the wetting agent for the organic titanium crosslinking agent is isopropyl alcohol, and the mass ratio of isopropyl alcohol to the organic titanium crosslinking agent is 1:1.
[0013] As an embodiment, the primer is divided into A component and B component, the primer A component is a mixture of the organic titanium crosslinking agent and the wetting agent for the organic titanium crosslinking agent, and the remaining composition belongs to the primer B component;
[0014] And / or, the topcoat is divided into A and B components, the topcoat A component is a mixture of the organic titanium crosslinking agent and a wetting agent for the organic titanium crosslinking agent, and the remaining components belong to the topcoat B component.
[0015] As an embodiment, the pH of the primer B component is 4.4-4.9;
[0016] And / or, the pH of the topcoat component B is 4.4-4.9.
[0017] As an embodiment, the concentration of the hydroxyethyl cellulose aqueous solution is 3 wt %.
[0018] As an embodiment, deionized water is heated to above 20° C., and hydroxyethyl cellulose is added under stirring until a uniform and transparent solution is obtained, thereby obtaining the hydroxyethyl cellulose aqueous solution.
[0019] <Second Aspect>
[0020] The present invention also provides a method for preparing the aforementioned cold spray ceramic coating, the method comprising the following steps:
[0021] Primer preparation:
[0022] S1, mixing the organic titanium crosslinking agent and the organic titanium crosslinking agent wetting agent uniformly to obtain a primer component A for standby use;
[0023] S2, mixing the silica sol, 1% NaOH solution, pigment, filler and dispersant evenly, grinding to a fineness of less than 20 μm, testing the pH value of the color paste, if it is less than 9.5, adjusting it to 9.5-10 with 1% NaOH solution; adding the hydroxyethyl cellulose aqueous solution, stirring evenly to obtain the color paste, and setting aside;
[0024] S3, mixing the methyltrimethoxysilane, acetic acid, leveling agent and deionized water, then adding the color paste, and mixing to obtain a ceramic primer B component;
[0025] And / or, Topcoat Preparation:
[0026] S4, mixing the organic titanium crosslinking agent and the organic titanium crosslinking agent wetting agent uniformly to obtain a topcoat component A for standby use;
[0027] S5. Evenly mix the methyltrimethoxysilane, acetic acid, leveling agent, non-stick additive and deionized water, then add silica sol and mix well to obtain component B of ceramic topcoat.
[0028] As an embodiment, in steps S3 and S5, the mixing is performed at 120-150 rpm for 6-8 hours.
[0029] <Third Aspect>
[0030] The present invention also provides a method for applying the aforementioned cold spray ceramic coating, the method comprising the following steps:
[0031] A1. Mix the primer components A and B evenly and spray them on the surface of the substrate;
[0032] A2. After the primer spraying is completed, mix the topcoat components A and B evenly, and then spray the topcoat on the primer surface in a wet-on-wet manner;
[0033] A3. Low temperature: 80-100℃×5-8 minutes; high temperature: 230-260℃×10-15 minutes, to complete the curing.
[0034] Compared with the prior art, the present invention has the following beneficial effects:
[0035] (1) An organic titanium crosslinker is added to the ceramic coating formula, which can undergo a crosslinking reaction with the -OH in the ceramic coating system. By adjusting the pH of the ceramic coating after aging to between 4.4 and 4.9, a cold-sprayable ceramic coating is prepared. After spraying at room temperature, the paint film achieves the effect of leveling and crosslinking at the same time. After crosslinking, the paint film loses its fluidity, and even if the substrate is suspended for spraying, no sagging will occur.
[0036] (2) Since the organic titanium crosslinker is a crosslinker for -OH and -COOH systems, after crosslinking reaction with the inorganic metal substrate and ceramic coating system, it can improve the adhesion between the ceramic coating and the substrate, and improve the crosslinking density and water resistance of the coating; since the paint film has good leveling during the crosslinking reaction, the paint film has a smooth appearance and the gloss is not affected. DETAILED DESCRIPTION
[0037] The present invention is described in detail below in conjunction with embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, some adjustments and improvements can also be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.
[0038] The cold spray ceramic coating of the present invention is divided into two layers, namely, a primer and a topcoat; wherein the primer is a color paint, and based on 100% of the total mass of the primer, the primer composition is as follows: silica sol: 26-28%, 1% NaOH solution: 4-5%, pigment: 10-12%, filler: 8-10%, 3wt% hydroxyethyl cellulose aqueous solution: 4-5%, dispersant: 1-1.5%, methyltrimethoxysilane: 20-22%, acetic acid: 5-6%, leveling agent: 1-2%, organic titanium crosslinking agent: 1-2%, a wetting agent (isopropanol) for the organic titanium crosslinking agent, the mass ratio of the wetting agent (isopropanol) to the organic titanium crosslinking agent is 1:1-1:1.5, and deionized water: the balance.
[0039] in,
[0040] Silica sol: The main film-forming substance of ceramic coatings, rich in -OH on the surface, is a common commercial product, such as Bindzil 2034DI from Akzo Nobel, ST-O-40 from Nissan Chemical, and Grace HS-40, etc.
[0041] 1% NaOH solution: pH value regulator for color paste. The pH value of the color paste will drop slightly during the grinding process and storage. When the pH value drops below 8.5 and approaches neutrality, the silica sol will gel and cause the color paste to deteriorate. Therefore, before grinding, the pH value of the color paste needs to be adjusted to between 9.5-10.5 with an alkaline solution. After grinding, the pH value of the color paste should be adjusted to above 9.5 to ensure that the color paste will not deteriorate due to the drop in pH value during storage.
[0042] Pigments: To give the paint different colors, ordinary inorganic pigments are used. Inorganic pigments have good temperature resistance and safety, such as titanium dioxide, ferromanganese black, iron oxide yellow, iron oxide red, cobalt blue, etc.
[0043] Filler: It can reduce the cost of coating and increase the solid content of coating. Common fillers are selected, such as mica powder, silica powder, silicon carbide, alumina powder, talcum powder, etc.
[0044] 3-3.5wt% hydroxyethyl cellulose aqueous solution: a relatively mild water-based paint thickener, with a small viscosity change in the pH range of 2-12, which can adjust the viscosity of ceramic paints, has very good transparency, excellent leveling, and is rich in -OH on the molecular chain surface, which can undergo a cross-linking reaction with an organic titanium cross-linking agent. Since the ceramic paint color paste is alkaline (about 8.5-10) and the finished ceramic paint is acidic (4.4-4.9), the pH value varies greatly. If other types of cellulose are used, the pH change will cause a large change in the paint viscosity, resulting in the inability to apply the paint. In addition, if the concentration of hydroxyethyl cellulose is lower than 3%, the effect of adjusting the paint viscosity is not good, and a large amount needs to be added, which will reduce the solid content of the paint, resulting in poor wear resistance of the coating, and further affecting the non-stick durability. If the concentration of hydroxyethyl cellulose is higher than 3.5%, the paint viscosity will increase too much. On the one hand, it is easy to block the gun during spraying, and the construction performance is poor; on the other hand, the leveling time is not enough, and the coating is cross-linked before it is fully leveled, which can easily cause the coating to have low gloss and poor decorative properties.
[0045] Dispersant: It reduces the dispersion time of pigments and fillers, stabilizes pigment dispersions, and improves pigment tinting power and hiding power, for example: BYK180, BYK190, BYK2010, BYK2001, etc.
[0046] Methyltrimethoxysilane: auxiliary film-forming substance. On the one hand, the hydrolysis and polymerization speed of methyltrimethoxysilane is fast, which can shorten the reaction time of ceramic coatings and improve the efficiency of ceramic coating maturation. On the other hand, Si is connected to three -OCH3, and three silanol groups (Si-OH) are formed after hydrolysis. After polymerization with silica sol, a coating with a three-dimensional cross-linked structure can be formed. The structure of the coating is compact and not easy to crack.
[0047] Acetic acid: a catalyst for the sol-gel reaction of ceramic coatings, which adjusts the pH value of ceramic coatings to between 4.4 and 4.9 after reaction. Methyltrimethoxysilane is hydrolyzed under acidic conditions and undergoes a polycondensation reaction with silica sol to produce ceramic coatings. Due to the different acidity and catalytic efficiency of different acids, if other acids such as formic acid, citric acid, benzoic acid, and hydrochloric acid are used as substitutes for this formula, the pH of the ceramic coating after aging will be less than 4.0, or even lower. On the one hand, the ceramic coating can be used for a very short time, usually less than 12 hours, and the paint film will dry out; on the other hand, the cross-linking reaction speed of the organic titanium cross-linking agent is too fast, the paint film does not level well, and the coating has low gloss.
[0048] Leveling agent: It helps the coating to form a flat, smooth and uniform coating during the drying process. For example: BYK-333, Dow Corning DC-57.
[0049] Organic titanium crosslinker: It is an environmentally friendly water-based coating crosslinker and adhesion promoter. It can react with various types of resins containing -OH and -COOH to improve the crosslinking density of the water-based system, improve adhesion, water resistance and other functions. For example: DuPont TM 371, etc. It can be stably stored in aqueous solution with pH value = 7-8. When pH value < 6 or pH value > 8 or temperature > 100°C, 371 will undergo a cross-linking reaction, and the reaction rate varies with changes in pH or temperature. TPT will generate titanic acid when it comes into contact with water, which will affect the pH value of the coating and is not suitable for the system of the present invention.
[0050] In ceramic coating system, the surface of silica sol, the main film-forming substance, is rich in -OH, and the auxiliary film-forming substance methyltrimethoxysilane forms silanol (-SiOH) after acidic hydrolysis. In addition, the molecular chain of thickener hydroxyethyl cellulose is also rich in -OH. Therefore, the organic titanium crosslinker can fully crosslink with the ceramic coating system to play a role.
[0051] Isopropyl alcohol: an organic solvent, used as a special wetting agent for organic titanium crosslinkers, mixed with organic titanium crosslinkers in a mass ratio of 1:1 to improve compatibility with water-based coatings.
[0052] In the cold spray ceramic coating of the present invention, the topcoat is colorless and transparent. Based on 100% of the total mass of the topcoat, the topcoat has the following composition: silica sol: 38-40%, methyltrimethoxysilane: 30-32%, acetic acid: 5-6%, leveling agent: 3-4%, non-stick additive: 3-4%, organic titanium crosslinking agent: 1-2%, a wetting agent for the organic titanium crosslinking agent (isopropanol), the mass ratio of the wetting agent to the organic titanium crosslinking agent is 1:1-1.5:1, and deionized water: the balance.
[0053] In topcoat,
[0054] Non-stick additives: improve the feel and non-stick performance of the coating, as well as the ease of cleaning. Non-stick additives with hydroxyl groups at the end of the molecular chain are preferred. They can participate in the reaction during the maturation of the ceramic coating and connect to the molecular chain in the form of chemical bonds, which can provide the ceramic coating with more lasting non-stick properties. Common commercial products, such as 3600 from Guangzhou Hanju Polymer Materials Co., Ltd. and K-766 from Guangdong Biaomei Fluorosilicone New Materials Co., Ltd.
[0055] The preparation steps of the cold spray ceramic coating and primer of the present invention are as follows:
[0056] (1) Preparation of 3 wt % hydroxyethyl cellulose aqueous solution: Weigh 97 g of deionized water and 3 g of hydroxyethyl cellulose. First, heat the deionized water to above 35° C. and gradually add the hydroxyethyl cellulose while stirring until it becomes a uniform and transparent solution. Set aside.
[0057] The solubility of hydroxyethyl cellulose in cold water is not high (<5wt%) and it dissolves slowly, but the solubility of hydroxyethyl cellulose can be significantly improved in hot water. After being completely dissolved, it becomes a colorless and transparent solution, which will not affect the color of the coating.
[0058] (2) Preparation of color paste: Mix silica sol, 1% NaOH solution, pigment, filler and dispersant evenly, grind to a fineness of less than 20 μm on a basket grinder, test the pH value of the color paste, if it is less than 9.5, adjust it to 9.5-10 with 1% NaOH solution, then add 3wt% hydroxyethyl cellulose aqueous solution, stir evenly and set aside.
[0059] The pH value of the color paste of ceramic coatings will drop slightly during grinding and storage. The degree of pH drop of different color pastes will also be different. When the pH value of the color paste part drops below 8.5 and approaches neutrality, the silica sol will gel and cause the color paste to deteriorate. Therefore, it is necessary to use an alkaline solution to adjust the pH value of the color paste part after grinding to 9.5-10 to ensure that the color paste will not deteriorate due to the decrease in pH value during storage. The viscosity of hydroxyethyl cellulose changes little in the pH range of 2-12, and the viscosity of the prepared color paste changes little, is stable and not easy to settle.
[0060] (3) Mix the organic titanium crosslinker and isopropyl alcohol in a weight ratio of 1:1 and set aside; the organic titanium crosslinker and isopropyl alcohol can improve the compatibility and stability with the water-based coating system. If the organic titanium crosslinker is directly added to the water-based coating, the coating will be delaminated, the crosslinking reaction will be insufficient, the curing speed of the coating will be slow, the adhesion will be slightly poor, and the water resistance will be poor.
[0061] (4) Methyltrimethoxysilane, acetic acid, a leveling agent, and deionized water are mixed evenly, and then the color paste of step (2) is added, and the ceramic primer is obtained after rolling at 120-150 rpm for 6-8 hours, and the pH value is 4.4-4.9.
[0062] The solution of step (3) should be mixed with the primer before construction and then applied immediately. Since the organic titanium crosslinker is a fast crosslinking curing agent for -OH and -COOH systems, and since the ceramic coating film-forming substances silica sol and methyltrimethoxysilane both have -OH after hydrolysis, and the surface of hydroxyethyl cellulose molecules is also rich in -OH, the organic titanium crosslinker can react with the ceramic coating system to undergo a crosslinking reaction; the crosslinking reaction rate is related to the pH of the system. Experiments have found that when the pH is between 4.4 and 4.9, the paint film can achieve the effect of leveling while crosslinking after spraying. After crosslinking, the paint film loses fluidity, and even if the substrate is suspended for spraying, sagging will not occur. When the pH is higher than 4.9, the crosslinking rate is slow, there is slight sagging, and the thickness of the suspended spray film is uneven; when the pH is lower than 4.4, the crosslinking rate is too fast, the paint film is not leveled well, and the gloss is low.
[0063] Since there is a certain amount of -OH on the surface of the inorganic metal substrate after sandblasting, the organic titanium crosslinking agent can also undergo a crosslinking reaction with the -OH on the surface of the substrate, thereby improving the adhesion of the paint film.
[0064] The preparation steps of the cold spray ceramic coating and the transparent topcoat of the present invention are as follows:
[0065] (1) Mix the organic titanium crosslinking agent and isopropanol in a weight ratio of 1:1 and set aside;
[0066] (2) Methyltrimethoxysilane, acetic acid, leveling agent, non-stick additive, and deionized water were mixed evenly, and then silica sol was added. After rolling at 120-150 rpm for 6-8 hours, a ceramic topcoat was obtained, and the tested pH was 4.4-4.9.
[0067] The construction method of topcoat is the same as that of primer. The solution in step (1) should be mixed evenly with the topcoat before construction and then applied immediately. Otherwise, they should be stored separately.
[0068] Embodiments 1 to 4
[0069] The present embodiments 1 to 4 provide a cold spray ceramic coating, which is divided into two layers, a primer and a topcoat; wherein the primer is a color paint and the topcoat is a transparent color; and its composition is shown in Table 1. Among them, 3wt% hydroxyethyl cellulose aqueous solution is prepared by weighing 97g of deionized water and 3g of hydroxyethyl cellulose, firstly heating the deionized water to above 20°C, gradually adding hydroxyethyl cellulose under stirring until it becomes a uniform and transparent solution, and then setting aside.
[0070] The preparation steps of the cold spray ceramic coating and primer of the present invention are as follows:
[0071] Preparation of primer component A: Mix the organic titanium crosslinker and isopropyl alcohol in a weight ratio of 1:1 and set aside.
[0072] Preparation of primer B component:
[0073] (1) Preparation of color paste: Mix silica sol, 1% NaOH solution, pigment, filler and dispersant evenly, grind to a fineness of less than 20 μm on a basket grinder, test the pH value of the color paste, if it is less than 9.5, adjust it to 9.5-10 with 1% NaOH solution, then add 3wt% hydroxyethyl cellulose aqueous solution, stir evenly and set aside.
[0074] (2) Methyltrimethoxysilane, acetic acid, a leveling agent, and deionized water were mixed evenly, and then the color paste of step (1) was added. After rolling at 120 rpm for 7 hours, a ceramic primer component B was obtained, and the pH value was 4.4-4.9.
[0075] The preparation steps of topcoat are as follows:
[0076] Preparation of topcoat component A: Mix the organic titanium crosslinking agent and isopropyl alcohol in a weight ratio of 1:1 and set aside.
[0077] Preparation of topcoat component B: Methyltrimethoxysilane, acetic acid, leveling agent, non-stick additive and deionized water were mixed evenly, and then silica sol was added. After rolling at 120 rpm for 7 hours, ceramic topcoat component B was obtained, and the tested pH was 4.4-4.9.
[0078] Comparative Examples 1 to 7
[0079] Comparative Examples 1 to 7 provide a ceramic coating, the composition of which is shown in Table 1; the preparation is the same as in Example 1. The preparation of 3 wt % hydroxymethyl cellulose aqueous solution, 3 wt % carboxyethyl cellulose aqueous solution, and 3 wt % hydroxypropyl methyl cellulose aqueous solution is also the same as in Example 1.
[0080] Table 1 Coating composition and dosage of Examples and Comparative Examples (wt.%)
[0081]
[0082]
[0083] Main performance test
[0084] The coatings prepared in the above embodiments and comparative examples were applied by the following method and then subjected to main performance tests. The construction process is as follows:
[0085] After mixing the primer components A and B evenly, pour them into a spray gun paint pot and spray them on the substrate surface within 1 minute;
[0086] After the primer spraying is finished, mix the topcoat components A and B evenly, then immediately pour them into another spray gun paint pot, and spray the topcoat on the primer surface in a wet-on-wet manner within 1 minute;
[0087] The sprayed workpiece is sent into the oven to complete curing, low temperature: 80-100℃*5-8 minutes; high temperature: 230-260℃*10-15 minutes, and the performance test is carried out after natural cooling. The thickness of the primer is 30-35μm, and the thickness of the topcoat is 5-8μm.
[0088] The test items and test methods involved in the main performance test of the coating are shown in Table 2:
[0089] Table 2
[0090]
[0091] The test results are shown in Table 3:
[0092] Table 3
[0093]
[0094] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.
Claims
1. A cold spray ceramic coating having a primer and a topcoat, characterized in that: Based on 100% of the total mass of the primer, the primer composition is as follows: silica sol: 26-28%, 1% NaOH solution: 4-5%, pigment: 10-12%, filler: 8-10%, hydroxyethyl cellulose aqueous solution: 4-5%, dispersant: 1-1.5%, methyltrimethoxysilane: 20-22%, acetic acid: 5-6%, leveling agent: 1-2%, organic titanium crosslinking agent: 1-2%, wetting agent for organic titanium crosslinking agent: 1-2%, and deionized water: the balance; Based on 100% of the total mass of the topcoat, the topcoat is composed of: silica sol: 38-40%, methyltrimethoxysilane: 30-32%, acetic acid: 5-6%, leveling agent: 3-4%, non-stick additive: 3-4%, organic titanium crosslinking agent: 1-2%, wetting agent for organic titanium crosslinking agent: 1-2%, and deionized water: the balance.
2. The cold spray ceramic coating according to claim 1, characterized in that: The organic titanium cross-linking agent is an aqueous titanate complex.
3. The cold spray ceramic coating according to claim 1, characterized in that: The wetting agent for the organic titanium cross-linking agent is isopropanol, and the mass ratio of isopropanol to the organic titanium cross-linking agent is 1:1-1.5:
1.
4. The cold spray ceramic coating according to claim 1, characterized in that: The primer is divided into A and B components, the primer A component is a mixture of the organic titanium crosslinking agent and the wetting agent for the organic titanium crosslinking agent, and the remaining composition belongs to the primer B component; And / or, the topcoat is divided into A and B components, the topcoat A component is a mixture of the organic titanium crosslinking agent and a wetting agent for the organic titanium crosslinking agent, and the remaining components belong to the topcoat B component.
5. The cold spray ceramic coating according to claim 4, characterized in that: The pH of the primer B component is 4.4-4.9; And / or, the pH of the topcoat component B is 4.4-4.
9.
6. The cold spray ceramic coating according to claim 1, characterized in that: The concentration of the hydroxyethyl cellulose aqueous solution is 3-3.5 wt %.
7. The cold spray ceramic coating according to claim 6, characterized in that: The deionized water is heated to above 20° C., and hydroxyethyl cellulose is added under stirring until it becomes a uniform and transparent solution, thereby obtaining the hydroxyethyl cellulose aqueous solution.
8. A method for preparing the cold sprayed ceramic coating according to any one of claims 1 to 7, characterized in that: The method comprises the following steps: Primer preparation: S1, mixing the organic titanium crosslinking agent and the organic titanium crosslinking agent wetting agent uniformly to obtain a primer component A for standby use; S2, mixing the silica sol, 1% NaOH solution, pigment, filler and dispersant evenly, grinding to a fineness of less than 20 μm, testing the pH value of the color paste, if it is less than 9.5, adjusting it to 9.5-10 with 1% NaOH solution; adding the hydroxyethyl cellulose aqueous solution, stirring evenly to obtain the color paste, and setting aside; S3, mixing the methyltrimethoxysilane, acetic acid, leveling agent and deionized water, then adding the color paste, and mixing to obtain a ceramic primer B component; And / or, Topcoat Preparation: S4, mixing the organic titanium crosslinking agent and the organic titanium crosslinking agent wetting agent uniformly to obtain a topcoat component A for standby use; S5. Evenly mix the methyltrimethoxysilane, acetic acid, leveling agent, non-stick additive and deionized water, then add silica sol and mix well to obtain component B of ceramic topcoat.
9. The method for preparing the cold sprayed ceramic coating according to claim 8, characterized in that: In steps S3 and S5, the mixing is performed at 120-150 rpm for 6-8 hours.
10. A method for applying the cold sprayed ceramic coating prepared according to the method of claim 8, characterized in that: The method comprises the following steps: A1. Mix the primer components A and B evenly and spray them on the surface of the substrate; A2. After the primer spraying is completed, mix the topcoat components A and B evenly, and then spray the topcoat on the primer surface in a wet-on-wet manner; A3, low temperature: 80-100℃×5-8 minutes; High temperature: 230-260℃×10-15 minutes to complete curing.
Citation Information
Patent Citations
Ceramic coating with good weather resistance and preparation method thereof
CN114456623A
Coating liquid give hydrophilic film, that inhibits soiling
DE19802392A1
Preparation process of ceramic mending agent
KR1019960022910A
